A review on dental whitening. (September 2020) - Alkahtani, Rawan; Stone, Simon; German, Matthew; Waterhouse, Paula
Abstract: Objectives: To provide a narrative review on vital dental whitening chemistry, toxicity and safety, vital dental whitening techniques, whitening systems, potential side effects of whitening and cyclic whitening using products with a range of concentrations and pH values. In addition, new developments and recommendations in the field of vital dental whitening will be presented to help clinicians understand the whitening process, its advantages, limitations, and the impact of whitening concentration and pH on enamel providing guidance in tailoring whitening treatments. Data: Data were gathered using the following keywords: dental whitening, roughness, hardness, sensitivity, hydrogen peroxide, whitening pH, whitening concentration, whitening chemistry, colour, and toxicity. Sources: An electronic search was performed using PubMed and Scopus databases. Bibliographic material from papers reviewed was then used to find other relevant publications. Conclusions: The effectiveness of vital dental whitening depends on many factors, such as the concentration/pH of the whitening agent, application duration, chemical additives, and re-mineralising agents used. Developing new whitening products and technologies such as nano-additives and alternative carrier systems is showing promising results, and might prove efficient in maximising whitening benefits by accelerating the whitening reaction and/or minimising expected reversible/irreversible enamel structural damage.